Development Local Culture-Based Science E-Supplements with “Gerakan Kebiasaan Anak Indonesia Hebat” on Additives Substance - Dinno Afriza; Hairida; Eni Mayasari (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Science learning on additive materials in schools has not yet utilized local culture as a learning context, resulting in a gap between students’ real-life experiences and the scientific concepts studied in the classroom. “Gerakan 7 Kebiasaan Anak Indonesia Hebat” carried out by the Ministry of Primary and Secondary Education which is designed as a strategy in building positive habits in learning, especially the habits of liking to teach, eating healthy and nutritious, and socializing. This study aims to develop a science e-supplement based on the local culture of Kapuas Hulu Regency and to examine its feasibility and user responses. The development model used is ADDIE, limited to the Development stage. The research procedures include needs analysis through teacher interviews, design and development of the e-supplement, and validation by material, media, and language experts. Teacher and student responses were collected using questionnaires. The validation results indicate that the e-supplement is categorized as highly feasible, with scores of 95.50% (material), 95.21% (media), and 95.83% (language). Teacher response results reached 91.66%, while student responses in small-scale and large-scale trials reached 97.34% and 98.62%, respectively. These findings show that the local culture-based science e-supplement is easy to use, engaging, and helps improve conceptual understanding. Therefore, the e-supplement is suitable to be used as supplementary teaching material in science learning.